The stability and post-buckling behaviour of stiffened plates in compression - Jhita, P. S. (Cranfield University, 1990)
The investigation reported in this thesis was carried out to examine the behaviour of stiffened plates subjected to uniform end compression using energy methods. The thesis begins with a short introduction, followed by a review of the relevant literature. The basic differential equations and energy expressions, using plate theory are then derived. The theoretical analysis of the mechanics of local, lateral and overall instability of asymmetrically and symmetrically edge stiffened plates is then presented. The analysis is then extended to investigate the behaviour of infinitely wide panels with stiffeners of deformable cross section. The results obtained from this analysis are used to highlight the shortcomings of using an infinitely wide panel model to predict the behaviour of a panel of a finite size through comparison with existing work. This is then followed by the analysis of a simply supported panel of finite size stiffened by stiffeners of rigid cross section. Plate theory was used to model the skin and beam theory to model the stiffeners. The results obtained from the analysis compared favourably with those already existing. The method is then extended to investigate the post buckling behaviour of simply supported plates and stiffened panels. The post-buckling behaviour of plates has received a considerable amount of attention since plates can carry loads beyond the critical load. The use of this additional strength.is of great importance to the design of aerospace, naval and civil engineering structures since considerable weight savings can be achieved. In comparison the post-buckling of light gauge integrally stiffened panels has received far less attention. Most of the published literature concentrates on the interaction between the local and overall buckling modes and the sensitivity of panels to geometrical imperfections when the local and overall buckling loads are nearly coincident. In all the above investigations, the overall buckling load for the panel is assumed to be equal to the Euler load for a pin-ended strut with the cross-section equal to the repeated panel cross- section. This implies that the transverse edges of the panels are assumed to be free. In general, stiffened panels are supported by a system of crossframes. A consequence of this layout is that lateral support is provided on all boundaries of the panel and therefore the wide strut model is invalid. In the present work the panels are assumed.to be simply supported along all four edges. It is shown that the post-buckling behaviour of these panels is substantially different to that of the wide strut model. The thesis finishes with a summary of the findings and a list of the main conclusions.